Creation of equal-spin triplet superconductivity at the Al/EuS interface. Issue 1 (December 2018) - Diesch, S.; Machon, P.; Wolz, M.; Sürgers, C.; Beckmann, D.; Belzig, W.; Scheer, E.
Abstract In conventional superconductors, electrons of opposite spins are bound into Cooper pairs. However, when the superconductor is in contact with a non-uniformly ordered ferromagnet, an exotic type of superconductivity can appear at the interface, with electrons bound into three possible spin-triplet states. Triplet pairs with equal spin play a vital role in low-dissipation spintronics. Despite the observation of supercurrents through ferromagnets, spectroscopic evidence for the existence of equal-spin triplet pairs is still missing. Here we show a theoretical model that reveals a characteristic gap structure in the quasiparticle density of states which provides a unique signature for the presence of equal-spin triplet pairs. By scanning tunnelling spectroscopy we measure the local density of states to reveal the spin configuration of triplet pairs. We demonstrate that the Al/EuS interface causes strong and tunable spin-mixing by virtue of its spin-dependent transmission. Spectroscopic evidence of equal-spin triplet Cooper pairs is still missing so far. Here, Diesch et al. propose a unique signature for the presence of equal-spin triplet pairs and experimentally reveal the spin configuration of triplet pairs at the Al/EuS interface.